ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI RASIO HUTANG PADA SEKTOR PERTANIAN, ANEKA INDUSTRI, DAN SUB-SEKTOR TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - , MARTHA FITRIA ARIANTI, Dr. Suad Husnan, MBA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research analyzes debt ratio of agriculture industry, miscellaneous industry, telecommunication industry and several factors that influence it. Several factors that influence debt ratio in this research are size, tangibility of assets, sales growth, profitability, business risk, liquidity. Population of this research are go public agriculture companies,miscellaneous industry companies, and telecomunication companies at Indonesia Stock Exchange. Sample determination using purposive sampling which 49 companies being analyzed. Data analysis using multiple regression analysis. The results of this research find that size, profitability, liquidity have significant effect to debt ratio. Unfortunately, there is no independent variable that consistently significant in all sectors.